'Storage Exhibitions' in Permanent Museum Collections: Interpretation, Critical Reflexivity and Democratisation. Issue 1 (2nd January 2021) - Crenn, Gaëlle
Abstract: 'Storage exhibitions' refer to staged storage areas displayed within a museum's permanent collection. What is the purpose of displaying these storage spaces within a museum's collection? I hypothesise that they are above all interpretive spaces intended to extend the dialogue between the museum and the public. A study of three cases (the National Museum of Australia in Canberra, Pinacoteca di Brera in Milan and Kunsthalle Mannheim) reveals the different functions performed by these exhibitions. They can show how museums work to preserve the heritage of their communities or they can give view on the work carried out by the museum's professionals itself. The study also illustrates how such exhibitions offer a lens through which to understand and explore a given institution's exhibitions and collections. Ultimately, each case is led by a sense of critical reflexivity that extends the display of museum objects to the display of the work carried out in the museum itself, hence opening up the nature of the museum's work to the general public.